THE ESSENCE OF SHARING JOINT PROPERTY AS A RESULT OF DIVORCE - ROYANI, ESTI; YUZURU, SHIMADA; GUNARTO; MASHDUROHATUN, ANIS (Sekolah Tinggi Ilmu Hukum Awang Long, 2019)
All individuals who have entered a household life certainly want the creation of a happy household, inner and outer prosperity and obtain the salvation of the world and the hereafter. Divorce is part of marriage, because there will be no divorce without first marriage. If in a divorce there is a dispute regarding the distribution of joint property, the resolution of a dispute regarding joint property can be submitted through the Religious Court. Property with husband and wife obtained during marriage, both husband and wife, have the same authority in the utilization of household life as well if there is a divorce between husband and wife either because of the death of one of the husband or wife (widowed) or divorce then the joint property have the same rights in the distribution of joint property.